Respiratory function in adult patients with spinal muscular atrophy treated with nusinersen – a monocenter observational study - Wurster, Claudia Diana; Uzelac, Zeljko; Dreyhaupt, Jens; Schuster, Joachim; Dorst, Johannes; Ludolph, Albert Christian; Wollinsky, Kurt (Frontiers in Neurology, 2024)
Background/Objective: Insufficiency of respiratory muscles is the most important reason for mortality in the natural history of SMA. Thus, improvement or stabilization of respiratory function by diseasemodifying therapies (DMT) is a very important issue.Methods: We examined respiratory function using forced vital capacity (FVC) in 42 adult SMA patients (2 SMA type 1, 15 SMA type 2, 24 SMA type 3, 1 SMA type 4, median age 37 years, range 17 -61 years) treated with nusinersen for a median of 22.1 months (range 2.1 to 46.7 months). Change in FVC was assessed using mixed effects linear regression models.Results: Baseline FVC differed significantly between SMA type 1 (4.0%, 8.0%), 2 (median 22.0%, IQR 18.0 -44.0), 3 (median 81.0%, IQR 67.0 -90.8) and respectively type 4 (84.0%) patients reflecting the heterogeneity of respiratory impairment based on the SMA type in adulthood (p<.0001). FVC remained stable during follow-up (mean -0.047, 95% CI -0.115 to 0.020, p=0.17); however, subgroup analysis showed an increase in FVC of type 2 patients (mean 0.144, 95% CI 0.086 to 0.202, p<.0001) and a decrease in FVC of type 3/4 patients (-0.142, 95% CI -0.239 to -0.044, p=0.005).The observed improvement in FVC in patients with SMA type 2 can be seen as a therapeutic response differing from the progressive decline typically seen in the spontaneous course.For SMA type 3/4 patients approaching normal spirometry at baseline, FVC may only be of limited use as an outcome parameter due to ceiling effects.